Virological Characterization of Critically Ill Patients With COVID-19 in the United Kingdom: Interactions of Viral Load, Antibody Status, and B.1.1.7 Infection. (24th May 2021) - Ratcliff, Jeremy; Nguyen, Dung; Fish, Matthew; Rynne, Jennifer; Jennings, Aislinn; Williams, Sarah; Al-Beidh, Farah; Bonsall, David; Evans, Amy; Golubchik, Tanya; Gordon, Anthony C; Lamikanra, Abigail; et al.
Abstract: Background: Convalescent plasma containing neutralizing antibody to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is under investigation for coronavirus disease 2019 (COVID-19) treatment. We report diverse virological characteristics of UK intensive care patients enrolled in the Immunoglobulin Domain of the REMAP-CAP randomized controlled trial that potentially influence treatment outcomes. Methods: SARS-CoV-2 RNA in nasopharyngeal swabs collected pretreatment was quantified by PCR. Antibody status was determined by spike-protein ELISA. B.1.1.7 was differentiated from other SARS-CoV-2 strains using allele-specific probes or restriction site polymorphism ( Sfc I) targeting D1118H. Results: Of 1274 subjects, 90% were PCR positive with viral loads 118–1.7 × 10 11 IU/mL. Median viral loads were 40-fold higher in those IgG seronegative (n = 354; 28%) compared to seropositives (n = 939; 72%). Frequencies of B.1.1.7 increased from <1% in November 2020 to 82% of subjects in January 2021. Seronegative individuals with wild-type SARS-CoV-2 had significantly higher viral loads than seropositives (medians 5.8 × 10 6 and 2.0 × 10 5 IU/mL, respectively; P = 2 × 10 −15 ). Conclusions: High viral loads in seropositive B.1.1.7-infected subjects and resistance to seroconversion indicate less effective clearance by innate and adaptive immune responses. SARS-CoV-2 strain, viral loads, and antibody status define subgroups for analysis of treatment efficacy. Abstract : Patients enrolled in a trial for convalescent plasma treatment were highly heterogeneous in terms of viral loads, infecting SARS-CoV-2 types, and antibody status, each potentially influencing treatment outcomes. B.1.1.7 infections were associated with higher viral loads and reduced clearance postseroconversion.